Limiting the term of office of village heads in an effort to prevent abuse of power - Siti Aminah; Tri Dian Aprilsesa; Marnita; Endah Mintarsih; Abunawas (Journal of Law Science, 2024)
The village head is a strategic position, because it is a position created to provide services to the community. Before reform, the terms of office of village heads were regulated in Law Number 5 of 1979 concerning Village Government. In this law, the term of office of a village head is 8 (eight) years and can be reappointed for 1 (one) term of office. Then, after the amendment to the 1945 Constitution, regulations regarding the term of office of village heads were regulated in various kinds of laws, namely Law Number 22 of 1999 concerning Regional Government, Law Number 32 of 2004 concerning Regional Government and the most recent is Law Number 6 of 2014 concerning Villages. There are differences in the term of office of the village head from the three laws, namely Law Number 22 of 1999 regulates that the term of office of the village head is 5 (five) years and can be two terms, then Law Number 32 of 2004 regulates the term of office of the village head, namely 6 (six) years and may be two terms. Meanwhile, Law Number 6 of 2014 regulates that the term of office of a village head is 6 (six) years and may be for three terms. Even though the village head's term of office is already long, it turns out that there is still dissatisfaction expressed by the village head and there is talk of increasing the village head's term of office to 9 (nine) years for each period. To prevent abuse of power, it is important to limit the term of office of village heads. If the village head's term of office is too long, the potential for fraud will become increasingly open.